(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This study investigates the application of financial derivatives as hedging strategies by Indian IT firms. It explores the types and extent of derivative usage, factors influencing hedging decisions, and the effectiveness of these strategies in mitigating financial risks. The research focuses on the top 3 IT companies (TCS, Wipro, and Infosys) for the financial year 2022-2023. The findings reveal the prevalent derivative instruments used for hedging by Indian IT firms and identify key factors influencing their decisions to hedge. The research also analyzes the impact of hedging on financial performance and risk exposure. This project contributes to the existing literature on corporate hedging practices by providing empirical evidence on the determinants of hedging behavior within the Indian IT sector. It offers valuable insights for investors, analysts, and policymakers by highlighting how Indian IT firms manage foreign exchange risk and other financial exposures using derivative instruments. The study also identifies potential limitations associated with derivative usage and suggests directions for future research.